2021
DOI: 10.17569/tojqi.796913
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Students’ Views About the Use of Argument-Driven Inquiry in the Science Courses

Abstract: The vision of science teaching is to train individuals who can produce and evaluate scientific knowledge by following the scientific processes like the scientists in order to understand and be able to produce solutions to the problems they encounter in real life. Ensuring this is only possible by using effective teaching methods. One of these methods is the argument-driven inquiry method. In parallel, the purpose of the study is to identify secondary students' views about the use of the argument-driven inquiry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Research on the educational attainment of slum dwellers has been carried out in India on occasion throughout the last twenty years, according to a review of relevant papers. Kalita [8] found that students from slum areas in Guwahati, India, had an average level of educational aspiration, but there was no significant difference between slum and nonslum students. This suggests that factors other than family background may be more critical in shaping educational aspirations.…”
Section: Literature Of Reviewsmentioning
confidence: 98%
“…Research on the educational attainment of slum dwellers has been carried out in India on occasion throughout the last twenty years, according to a review of relevant papers. Kalita [8] found that students from slum areas in Guwahati, India, had an average level of educational aspiration, but there was no significant difference between slum and nonslum students. This suggests that factors other than family background may be more critical in shaping educational aspirations.…”
Section: Literature Of Reviewsmentioning
confidence: 98%
“…The main goal of these curricula is science literacy, which is crucial for society. Science literacy individuals are those who produce knowledge, apply th is knowledge in This learning method, as illustrated in Figure 1, emphasizes both the practical components of laboratory work (posing questions, designing methods) and the communication of scientific findings (reasoning, writing) to foster students' science literacy (Çetin & Eymur, 2018;Kaçar & Balım, 2018 ;2021a). In other words, it integrates argumentation with laboratory-based teaching for a comprehensive view (Fakhriyah & Rusilowati, 2021;Walker & Sampson, 2013a;2013b).…”
Section: Introductionmentioning
confidence: 99%